The Challenges of Islamic Fintech Growth in Indonesia: A Bibliometric Analysis - M. Nur Ikhwan; Awaludin Taufiq; Aditya Darmawan; Inna Khoridatul Bahiya; Ikin (Jurnal Ilmu Ekonomi Terapan, 2026)
Objective: The aim of this study is to explore the dynamics and difficulties associated with Islamic fintech by integrating the emerging themes from the existing literature. Design/Methods/Approach: Using bibliometric analysis and VOSviewer, the research examines 686 publications from the CrossRef database (2018-2024) through keyword co-occurrence networks, overlay visualization, and density analysis. Findings: The intellectual structure reveals a dense collaboration network centered on core actors, with B. Koderi and Basyar Syaripudin as the most active nodes, while Gunarto A emerges as the most productive author. The co-word structure indicates that Islamic fintech scholarship is organized around a problem-solving logic with "challenge – innovation – development" framing most discussions, consistently linked to regulation, legal protection, Sharia principles, and technology adoption. The overlay visualization demonstrates a maturing trajectory where 2022 focused on conceptual framing, late 2022–2023 shifted to implementation bottlenecks, and 2023–2024 consolidated behavioral themes such as adoption, intention, and MSMEs. However, regulatory effectiveness and Sharia governance remain insufficiently developed as objects of systematic evaluation and are not yet firmly integrated with innovation-adoption debates. Originality/Value: The originality lies in its integrative bibliometric mapping approach specifically focused on a specific country  context, combining keyword co-occurrence networks, overlay visualization, and density analysis to map the entire intellectual structure. It uniquely identifies the "challenge – innovation – development" framing as the dominant logic and highlights the core–periphery structure of author collaborations, offering novel understanding of knowledge production in this emerging field. Practical/Policy implication: The government and the Financial Services Authority (OJK) need to focus on strengthening regulations, governance, and technology-based innovation in the Sharia sector, including regulatory sandboxes, digital literacy, and research and technology collaboration to support a sustainable Sharia fintech ecosystem.